Study on haplotype diversity of Y-STR loci of the Kinh population in Vietnam - Tuan Toan, Trinh; Le Loi, Vu; Quoc Khanh, Ha; Quang Vinh, Nguyen; Quang Huy, Nguyen (VNU Journal of Science: Natural Sciences and Technology, 2017)
The study was carried out to determine allele frequencies of Y-STRloci in order to apply in the statistical validation of forensic case and paternal lineages. 17 Y-STR loci were co-amplified (including: DYS19, DYS389I, DYS389II, DYS390, DYS391, DYS392, DYS393, DYS385, DYS437, DYS438, DYS439, DYS448, DYS456, DYS458, DYS635, and GATAH4) using DNA genome extracted from blood, hair root and finger nail samples of 205 unrelated men of Kinh population in the North and South of Vietnam. The studied population shows that a relatively close relationship between the Jiangxi (Han) and Jiangsu (Han) populations in China and the Han population in Taiwan. Compared to other population with geographic locations far removed from Vietnam and historically and culturally diverse, there are significant differences as with Americans (Rst = 0.3836, P <0.0001); The Germans (Rst = 0.3562, p = -1.0000); The Romans (Rst = 0.2918, p = -1.0000) or Ethiopian (Rst = 0.3139, p = -1.0000) and particularly significant differences with Nigerians (Rst = 0.5084, p = -1.0000). The genetic diversity indexes at each locus and the haplotypes were examined; Genetic distances between the King population in this study and neighboring populations and geographically remote populations are consistent with the migration history.